Optimalisasi Pemanfaatan Tanaman Herbal Sebagai Obat Anti-Gout Arthritis Sebagai Upaya Pencegahan Penyakit Gagal Ginjal - Evi Lusiana; Nia Savitri Tamzil; Desi Oktariana; Gita Dwi Prasasty; Bintang Fajarullah; Bella Puspita Aziatri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Health education about the benefits of herbal plants as anti-gout arthritis drugs needs to be done to help people increase their knowledge so that they can apply wise actions and attitudes that can improve their quality of life. The purpose of community service activities is to find out the effect of health socialization on the use of herbal plants on gout by assessing the increase in knowledge, attitudes, actions of participants and assistance in making ginger tea as a prevention of gout arthritis, as well as conducting gout screening tests. Methods of community service activities in the form of counseling, outreach, and education as well as assistance in making ginger medang which will then be evaluated with pre and post counseling questionnaires. The number of participants 30 people are people who live in the work area of the Palembang Kertapati Health Center. An indicator of the success of counseling is an increase in the knowledge, attitudes and actions of community service participants. In the results of the study, it was known that the level of knowledge before socialization and education was 36.7% and increased after socialization (86.7%); attitude of participants before socialization 80% after socialization increased to 100%; action before socialization 63.3% after socialization 100%. It is known that there is an influence from education and outreach in the form of increasing knowledge, attitudes and actions of the community at the Kertapati Health Center, Palembang City, South Sumatra so that a follow-up program is needed in the form of intensive counseling for health center cadres as the spearhead of information on a wider range of people.